Expression and purification of human respiratory syncytial virus recombinant fusion protein - Arcuri, Helen A. [UNESP]; Apponi, Luciano H. [UNESP]; Valentini, Sandro Roberto [UNESP]; Durigon, Edison L.; Azevedo, Walter F. de; Fossey, Marcelo Andrés [UNESP]; Rahal, Paula [UNESP]; de Souza, Fatima P. [UNESP] (Academic Press Inc. Elsevier B.V., 2008)
The Human Respiratory Syncytial Virus (HRSV) fusion protein (F) was expressed in Escherichia call BL21A using the pET28a vector at 37 degrees C. The protein was purified from the soluble fraction using affinity resin. The structural quality of the recombinant fusion protein and the estimation of its secondary structure were obtained by circular dichroism. Structural models of the fusion protein presented 46% of the helices in agreement with the spectra by circular dichroism analysis. There are only few studies that succeeded in expressing the HRSV fusion protein in bacteria. This is a report on human fusion protein expression in E. call and structure analysis, representing a step forward in the development of fusion protein F inhibitors and the production of antibodies. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Fusion protein; Purification; Dichroism analysis; Molecular modeling; Expression